CRETACEOUS TERTIARY PHENOMENA IN THE CONTEXT OF SEAFLOOR REARRANGEMENTS AND P(CO2) FLUCTUATIONS OVER THE PAST 100 M.Y - Liu Y.G.; Schmitt R.A. (My University, 1996)
Both the bolide impact hypothesis and the volcanism hypothesis suggest, as one of the major environmental consequences, the release of large amounts of SO2 and CO2 into the atmosphere, with consequent lowering of the pH of ocean water. In the study of rare earth elements (REEs) in seawater and in carbonate sediments, we found that the Ce in seawater is depleted relative to other REEs due to the partial oxidation of Ce3+ to Ce4+ by dissolved oxygen. This oxidation is enhanced by the formation of highly insoluble Ce(OH)4 and its removal from seawater. The relative Ce depletion is expressed as the Ce anomaly, CeA*. A quantitative expression for relating CeA* with pH andPO2 has been derived. Owing to the involvement of OH- in this process, CeA* is essentially controlled by the pH of seawater. The REE pattern in seawater is preserved in carbonate sediments. Therefore, the Ce anomalies in marine carbonate sediments provide a unique tool for recording pH changes in paleo-ocean water. Furthermore, the pH of ocean water is controlled by the partial pressure of CO2, PCO2, in the atmosphere; therefore, the corresponding PCO2 changes are derived. About 340 Pacific carbonate sediment samples have been studied by INAA (Instrumental Neutron Activation Analysis). Three major CeA* peaks at #17, #53, and #63 Ma, as well as two minor peaks at 64.6 and 65.2 Ma, were found. The correspondence between observed CeA* major peaks and the enhanced hydrothermal activity associated with tectonic seafloor rearrangements at these times suggests that the pH of the deep (>600 m) Pacific water was lowered by CO2 generated by enhanced hydrothermal activity. Manganese and Co, which are highly enriched in hydrothermal solutions, closely follow the CeA* pattern. This is strong evidence that the CeA* peaks are related to the elevated levels of hydrothermal activity. The absence of CeA* changes at the K/T (Cretaceous/Tertiary)-Ir boundary (≡65.0 Ma) suggests that the proposed release of SO2 and CO2 by cratering has not significantly lowered the pH of deep ocean water. Our analysis supports only #5x increase of atmospheric CO2 by the putative K/T bolide impact into a #3 km thick carbonate terrane. We did not observe the pH changes of deep ocean water which could be unambiguously attributed to the volcanic release of SO2 and CO2 from the Deccan Trap flows. The #5 ka (FWHM, Full Width Half Maximum) CeA* peak #0.2 m.y. before the K/T-Ir boundary is too short to account for the Deccan Trap eruptions. Of course, our results do not rule out surface water pH changes due to either the Urey-comet or Alvarez-asteroid impact or volcanism. The elevated PCO2 of #1.9xP0CO2 (P0CO2 ≡ present pressure) which started #0.75 Ma after the K/T-Ir event and lasted for #2.3 m.y., may be one of the factors responsible for the extended period of extinctions across the K/T boundary for some species. If any species of dinosaurs lived beyond the K/T-Ir event, we predict that they would not have survived the greenhouse effect that very likely occurred between 64.25-62.0 Ma.Our PCO2 absolute values are in general much lower than the theoretical values suggested by Berner (1990, 1993) during the Phanerozoic except for the Carboniferous and very late Cenozoic where our estimates of #1.0x P0CO2 agree with Berner's. Also, ourPCO2 values are lower than CO2 estimates derived from paleosol carbonate studies (e.g., Cerling, 1992; Mora et al., 1991).
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая